The innocent man - Grisham, John. (New York : Dell, 2006)
A true tale about murder and injustice in a small town. Chronicles the story of Ron Williamson, how he was arrested and charged with a crime he did not commit, how his case was (mis)handled and how an innocent man was sent to death row.
Keywords: Williamson, Ronald Keith, -- 1953-2004 -- Trials, litigation, etc; Trials (Murder) -- Oklahoma; Judicial error -- Oklahoma; Capital punishment -- Oklahoma